Prognostic impact of micrometastasis in patients with esophageal cancer - Włodarczyk, Janusz; Rudnicka-Sosin, Lucyna; Obarski, Piotr (Polish Journal of Pathology, 2023)
Squamous cell carcinoma (SCC) of the esophagus and adenocarcinoma of the esophago-gastric junction (AEG) are diseases with poor prognosis. Despite radical surgery having been carried out, many patients are at risk of cancer recurrence, especially with the presence of metastases in the lymph nodes. The study involved 60 patients suffering from SCC and AEG who had lymph nodes surgically removed between 2012 and 2018. Only lymph nodes with N0 status were subjected to immunohistochemistry examination. Histopathological criteria were used for the diagnosis of micrometastases (MM), defined as tumor cells or cell clusters of 0.2–2 mm diameter in the lymph node and tumor cell microinvolvement defined as free-floating neoplastic cells or cell clusters within the sub-capsular sinus or intramedullary sinuses of the lymph node. A total of 1130 lymph nodes were removed during surgery, with an average of 22 lymph nodes per patient (range 8–58). Micrometastases were found in 7 (11.66%) patients: 6 (10.0%) with AEG and 1 (1.66%) with SCC, representing a statistically significant difference p = 0.017. Multivariate analysis of the study group did not confirm the dependence of the MM on the T features ( p = 0.7) or G ( p = 0.5). In a Cox regression analysis, MM were not a risk factor for death, HR: 2.57 (0.95; 7.00), p = 0.064. There was no difference in overall survival for patients with MM (N (+)) and those without (N0), p = 0.055, but there was a statistically significant difference in time of relapse between patients with and without MM ( p = 0.049). Patients with the N (+) status are at high risk of cancer recurrence, and therefore we believe that complementary treatment should be considered in this group.